Humanism Civilization in the Perspective of Islamic History: Semantic Study of the Word Da’wa in the Qur’an - M. Yakub (Proceedings of International Conference on Da'wa and Communication, 2019)
This paper discusses about humanism civilization in the perspective of Islamic history. The approach taken in this journal is the historical narrative method by looking at universal values that favor human interests, expressed in a mindset, by not distinguishing on the basis of ethnicity, religion, skin color, and belief systems and religion. In addition, the author also explains that many aspects of humanity are recorded in Islamic history such as futuh mecca (conquerization of mecca). The author describes there are 4 leaders of Islamic leaders who describe humanitarian events contained in the history of Islam. This certainly awake and give direction to aspects relating to the general needs of humans including justice, equality (egalitarian) love and compassion, generosity, obedience to principles / law, environmental peace to the principles of chivalry and heroism. These universal principles are upheld and expressed by the Prophet Muhammad in his life and that is what he taught to his friends so that they will be passed on to the Muslims afterwards. The presence of this humanist civilization is like an oasis that gives thirst satisfaction to people who have the character of wisdom and have high ideals that all civilizations should elevate the degree of humanity. The impact of humanism civilization in the perspective of Islamic history is very useful because it refers to the principles of the Qur'an that give a universal message that can build humanism civilization that is embodied in the trajectory of Islamic history and continue the values of humanism's great and noble civilization.